2017
DOI: 10.1007/s11882-017-0704-3
|View full text |Cite
|
Sign up to set email alerts
|

Rural Asthma: Current Understanding of Prevalence, Patterns, and Interventions for Children and Adolescents

Abstract: Rural children experience factors unique to location that impact asthma development and outcomes, including housing quality, cigarette smoke exposure, and small/large-scale farming. Additionally, there are challenging barriers to appropriate asthma care that frequently are more severe for those living in rural areas, including insurance status, lack of primary care providers and pulmonary specialists, knowledge deficits (both patient and provider), and a lack of culturally tailored asthma interventions. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Telemedicine is capable to overcome the distance and safety barriers in this context and might be as effective as in-person visits for outpatient management of asthma (2), enabling mild to moderate-severe patients to get the supportive care they need. Several authors documented that virtual visits (VV), that could be either video or phone calls, for asthma patients allow positive outcomes, such as more symptom-free days and fewer emergency department visits or hospitalizations, improving asthma control (3,4). Moreover, it was demonstrated that VV are comparable to in-person visits, enabling its occasional replacement with same outcomes in asthma control (5).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is capable to overcome the distance and safety barriers in this context and might be as effective as in-person visits for outpatient management of asthma (2), enabling mild to moderate-severe patients to get the supportive care they need. Several authors documented that virtual visits (VV), that could be either video or phone calls, for asthma patients allow positive outcomes, such as more symptom-free days and fewer emergency department visits or hospitalizations, improving asthma control (3,4). Moreover, it was demonstrated that VV are comparable to in-person visits, enabling its occasional replacement with same outcomes in asthma control (5).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has highlighted the disproportionate asthma burden among urban children. However, recent research has shown a similar asthmarelated health burden in rural areas, especially among rural African American communities [37][38][39][40][41][42][43][44]. Risk factors for asthma ED visits include factors at an individual level, in addition to socioenvironmental factors at family, neighborhood, and even regional or administrative levels, making them difficult to disentangle.…”
Section: Motivating Datamentioning
confidence: 99%
“…In North Carolina (NC), racial disparities in asthma morbidity reflect national trends: for example, among children ages 0–14, the number of asthma‐related hospital discharges in American Indian children is greater than 3.4 times the number in White children (245 vs. 71.8 per 100,000, respectively; Bell, Foglia, & Ries, 2017). Concentrated largely in the least resourced counties in rural Southeastern NC, American Indian children are at particular risk based on geographic disparities in asthma and asthma morbidities burdening rural and impoverished counties disproportionately (Dieu, Kearney, Bian, Jones, & Mohan, 2018; Estrada & Ownby, 2017). Achieving better asthma control in high‐risk groups such as American Indians is a practical step toward narrowing the racial disparities gap in childhood asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Social, economic, and physical environmental factors unique to rural minority communities can create additional challenges in the management of asthma in rural minority children. Beyond disproportionate exposures to poor quality housing, tobacco smoke, and agriculture, rural families experience additional barriers that include lack of insurance, less access to healthcare services, and adverse socioeconomic conditions (Estrada & Ownby, 2017). Focusing on common, yet avoidable, asthma triggers in the child's physical environment within parents' control (e.g., environmental tobacco smoke) may improve asthma control in children (Abreo, Gebretsadik, Stone, & Hartert, 2018).…”
Section: Introductionmentioning
confidence: 99%